2010
DOI: 10.1161/hypertensionaha.109.138420
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Degradation of Angiotensin II With Recombinant Angiotensin-Converting Enzyme 2

Abstract: Abstract-Angiotensin (Ang)-converting enzyme 2 (ACE2) cleaves Ang II to form Ang-(1-7). Here we examined whether soluble human recombinant ACE2 (rACE2) can efficiently lower Ang II and increase Ang-(1-7) and whether rACE2 can prevent hypertension caused by Ang II infusion as a result of systemic versus local mechanisms of ACE2 activity amplification. rACE2 was infused via osmotic minipumps for 3 days in conscious mice or acutely in anesthetized mice. rACE2 caused a dose-dependent increase in serum ACE2 activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
321
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 297 publications
(361 citation statements)
references
References 33 publications
27
321
1
4
Order By: Relevance
“…ANG 1-7 opposes many ANG II-mediated actions, particularly vasoconstriction and vascular smooth muscle cell proliferation (31). Recently, administration of recombinant human Ace2 was reported to attenuate ANG II-dependent and pressure overloadinduced hypertension and myocardial remodeling as well as renal injury in Ace2 knockout mice (42,45,46), further supporting an important counterregulatory role of Ace2 in ANG II-induced heart and renal disease.The present study sought to determine whether a type 1 diabetic mouse model (Akita mice) in which rat Agt (rAgt) is overexpressed in the RPTCs would incur increased development of hypertension and nephropathy and whether RAS blockade could reverse these changes by normalizing renal Ace2 expression. …”
mentioning
confidence: 89%
See 1 more Smart Citation
“…ANG 1-7 opposes many ANG II-mediated actions, particularly vasoconstriction and vascular smooth muscle cell proliferation (31). Recently, administration of recombinant human Ace2 was reported to attenuate ANG II-dependent and pressure overloadinduced hypertension and myocardial remodeling as well as renal injury in Ace2 knockout mice (42,45,46), further supporting an important counterregulatory role of Ace2 in ANG II-induced heart and renal disease.The present study sought to determine whether a type 1 diabetic mouse model (Akita mice) in which rat Agt (rAgt) is overexpressed in the RPTCs would incur increased development of hypertension and nephropathy and whether RAS blockade could reverse these changes by normalizing renal Ace2 expression. …”
mentioning
confidence: 89%
“…ANG 1-7 opposes many ANG II-mediated actions, particularly vasoconstriction and vascular smooth muscle cell proliferation (31). Recently, administration of recombinant human Ace2 was reported to attenuate ANG II-dependent and pressure overloadinduced hypertension and myocardial remodeling as well as renal injury in Ace2 knockout mice (42,45,46), further supporting an important counterregulatory role of Ace2 in ANG II-induced heart and renal disease.…”
mentioning
confidence: 97%
“…Nevertheless, exogenous supplementation of ACE2 by gene transfer decreased BP in SHR hypertensive rats, 38 and recombinant ACE2 treatment attenuated Ang II-induced hypertension specifically. 49 Thus, ACE2 clearly must function as a negative regulator of the RAS in BP control. In addition to BP regulation, ACE2 delivery has also shown beneficial effects on atherosclerosis in animal models, suggesting that ACE2 confers endothelial protection.…”
Section: Ace2 As a Negative Regulator Of The Ras In The Cardiovasculamentioning
confidence: 99%
“…It is demonstrated that ACE2 cleaves AngII to form Ang-(I-VII) with a high catalytic efficiency; whereafter, Ang-(I-VII) exerts opposing actions to those of AngII by inhibiting vasoconstriction and cell proliferation and consequently protect the retina. 16,25 The reduction of serum level of Ang-(I-VII) may reduce the protective function on retina and cause the occurrence and development of DR. In this study, we found that ACE2 gene variants were probably involved in the pathogenesis of DR and PDR in the Chinese female T2DM cohort.…”
Section: Discussionmentioning
confidence: 99%